Single and multi-photon events with missing energy in e+e- collisions at 161 GeV < √s < 172 GeV - Dova, Maria Teresa (1997)
A search for single and multi-photon events with missing energy is performed using data collected at centre-of-mass energies between 161 GeV and 172 GeV for a total of 20.9 pb 1 of integrated luminosity. The results obtained are used to derive the value for the vvy(y) cross section as well as upper limits on new physics processes.